Influence of urban landscapes on population dynamics in a short-distance migrant mosquito: evidence for the dengue vector Aedes aegypti. - Ryan R Hemme; Clayton L Thomas; Dave D Chadee; David W Severson (Public Library of Science (PLoS), 2010)
Dengue viruses are endemic across most tropical and subtropical regions. Because no proven vaccines are available, dengue prevention is primarily accomplished through controlling the mosquito vector Aedes aegypti. While dispersal distance is generally believed to be approximately 100 m, patterns of dispersion may vary in urban areas due to landscape features acting as barriers or corridors to dispersal. Anthropogenic features ultimately affect the flow of genes affecting vector competence and insecticide resistance. Therefore, a thorough understanding of what parameters impact dispersal is essential for efficient implementation of any mosquito population suppression program. Population replacement and genetic control strategies currently under consideration are also dependent upon a thorough understanding of mosquito dispersal in urban settings.We examined the effect of a major highway on dispersal patterns over a 2 year period. A. aegypti larvae were collected on the east and west sides of Uriah Butler Highway (UBH) to examine any effect UBH may have on the observed population structure in the Charlieville neighborhood in Trinidad, West Indies. A panel of nine microsatellites, two SNPs and a 710 bp sequence of mtDNA cytochrome oxidase subunit 1 (CO1) were used for the molecular analyses of the samples. Three CO1 haplotypes were identified, one of which was only found on the east side of the road in 2006 and 2007. AMOVA using mtCO1 and nuclear markers revealed significant differentiation between the east- and west-side collections.Our results indicate that anthropogenic barriers to A. aegypti dispersal exist in urban environments and should be considered when implementing control programs during dengue outbreaks and population suppression or replacement programs.